Why healthcare workers are sick of TB. (March 2015) - von Delft, Arne; Dramowski, Angela; Khosa, Celso; Kotze, Koot; Lederer, Philip; Mosidi, Thato; Peters, Jurgens A.; Smith, Jonathan; van der Westhuizen, Helene-Mari; von Delft, Dalene; Willems, Bart; Bates, Matthew; et al.
Highlights: Healthcare workers (HCWs) are at an increased risk of tuberculosis (TB), especially drug-resistant TB. TB and HIV stigma delays access to care and prevents disclosure, hiding the problem. Progressively incurable TB is an occupational and public health emergency. HCWs are a scarce and precious resource that must be protected. We need urgent strengthening of TB infection control, diagnosis, and treatment. Summary: Dr Thato Mosidi never expected to be diagnosed with tuberculosis (TB), despite widely prevalent exposure and very limited infection control measures. The life-threatening diagnosis of primary extensively drug-resistant TB (XDR-TB) came as an even greater shock. The inconvenient truth is that, rather than being protected, Dr Mosidi and thousands of her healthcare colleagues are at an increased risk of TB and especially drug-resistant TB. In this viewpoint paper we debunk the widely held false belief that healthcare workers are somehow immune to TB disease (TB-proof) and explore some of the key factors contributing to the pervasive stigmatization and subsequent non-disclosure of occupational TB. Our front-line workers are some of the first to suffer the consequences of a progressively more resistant and fatal TB epidemic, and urgent interventions are needed to ensure the safety and continued availability of these precious healthcare resources. These include the rapid development and scale-up of improved diagnostic and treatment options, strengthened infection control measures, and focused interventions to tackle stigma and discrimination in all its forms. We call our colleagues to action to protect themselves and those they care for.